Drought stress - related functional characterization of transcription factor GmNAC085 in soybean - Khanh Hoa, Tran Thi; Ngoc Tuyet, Huynh; Phuong Thao, Nguyen; Lan Xuan, Hoang Thi (Vietnam Journal of Biotechnology, 2020)
Studies on soybean GmNAC085 transcription factor revealed that the gene expression in plants was induced by water shortage treatments and its overexpression in the model plant Arabidopsis displayed improved plant tolerance characteristics towards drought stress. In this study, we continued analyzing the biological functions of GmNAC085 using transgenic soybean system overexpressing GmNAC085 gene, by targeting at a number of plant physiological features and biochemical activities in response to limited water growing condition. Compared to the wild-type, the transgenic line demonstrated that it possessed stress tolerance characters, including enhanced elongation of taproot, minimized reduction of shoot growth, lower intracellular H2O2 content and stronger peroxidase enzyme activity under drought condition. The results of this study therefore suggest the transgenic plants had better drought tolerance and the GmNAC085 plays important role in aiding plants to cope with water deficit condition, probably via regulating the growth of roots and shoots, and activities of reactive-oxygen-species- scavenging enzymes.